FLEKSIBILITAS DAN INOVASI DI SEKTOR PUBLIK - Muhaidin Masuku (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2021)
ABSTRACTBasically, humans need service, the concept of service will always be in human life. So that public services are essentially the fulfillment of the rights of basic needs of the state to the people. The main thing that becomes an indicator that bablik service providers have been responsive to the community is the emergence of service innovation. Innovation is expected to be a strategy in increasing the leverage of organizational performance both in producing products and services. The fact is that public service innovation activities that are effective, efficient and productive, can still lead to irregularities in their implementation. Starting from services that are not in line with community expectations. There are also irregularities in the uncertainty of time of service, uncertainty of cost. Besides that, the community has not been able to provide suggestions and criticisms for the service they have received. Illegal levies, disregard for the rights and dignity of service users also indicate deviations in public services. The purpose of this paper is to examine a variety of literature and observe and analyze innovations in the public sector that occur in the country to the regions. From the results of a review of some of the literature it turns out there are still constraints in developing even to apply innovation in the public sector. This obstacle occurs not only in large conditions, for example in a country, but also in a small region, namely in an area. This downturn is basically the same. including lack of support from direct superiors, systems that do not support the management of ideas, poor facilities, at least an emphasis on dissemination and commercialization, a system of rewards and incentives that are inadequate, procedures that are rigid and inefficient because of work based on existing rules. Keywords: Innovation, Public Sector.